Konsep Administrasi Laboratorium Pendidikan Teknologi Kejuruan di Departemen Teknik Elektro Universitas Negeri Padang - Dina Salsa Fauzia; Riki Mukhaiyar (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2022)
This study aims to determine management and its effect on improving management performance in the Laboratory of the Department of Electrical Engineering. As for the method used, namely the qualitative method with an interview. The subjects of the study were two Laboratory at the Department of Electrical Engineering, Faculty of Engineering, Padang State University. The procedure for collecting information is carried out by using the procedures for interviews with two laboratory workers and documentation is carried out to obtain information in the form of photos or supporting documents as research support. Before conducting an interview, of course, it is necessary to conduct a validity / feasibility test by the validator to produce the correct research instrument. After the interview results were obtained, the researcher then conducted an analysis of the results of the interview with the informant. Procedures in data analysis use several techniques such as data collection, data reduction, data presentation, and drawing conclusions. For the validation of data, a triangulation technique is used, which is to compare the results of the interview with the content of related documents. Until, it can be concluded that the administration in the Laboratory of the Department of Electrical Engineering, Padang State University is in accordance with the Standard Operating Procedures (SOP) provided by the Department and increases the need for tools to improve the performance of laboratory management.